Peduli lingkungan melalui kegiatan bersih-bersih di UIN Walisongo bersama IKANMAS (Ikatan Mahasiswa Semarang) - Mutma’inah, Mutma’inah; K, Dewi Fatimatul; Masithoh, Dewi; Refalenawati, Refalenawati; Nisa’, Retna Choirotun; Azzahra, Dayssyifa Jingga; Kalsum, Tsalatsa Alifa (Jurnal PADE: Pengabdian & Edukasi, 2025)
Environmental cleanliness is a key aspect that reflects the quality of life and shared responsibility in preserving nature. This activity aims to raise student awareness of the importance of cleanliness of the campus environment through clean-up activities involving collaboration between the Semesta Youth group and the regional organization IKANMAS (Ikatan Mahasiswa Semarang). This program was implemented at UIN Walisongo Semarang Campus, especially in the Jati Park and Juras area, which are known to have cleanliness problems due to low student awareness. The methods used included preparation, implementation, and monitoring stages, including hygiene education, field observations, and direct action to clean the campus environment. The results of the activities showed that the actions and education carried out succeeded in increasing the awareness of students and the surrounding community of the importance of maintaining cleanliness. In addition, the cleaning action succeeded in reducing the pile of garbage in the campus area, creating a cleaner and more comfortable environment to support learning activities. Positive changes were also seen in the behavior of students who began to make better use of cleaning facilities and adopt the habit of sorting waste. Through this collaboration, the program succeeded in building a sustainable culture of environmental care, creating synergies between students, local organizations, and the campus